Agent-Based Technologies and Applications for Enterprise Interoperability International Workshops ATOP 2009, Budapest, Hungary, May 12, 2009, and ATOP 2010, Toronto, ON, Canada, May 10, 2010, Revised Selected Papers - Fischer, Klaus.; Fischer, Klaus.; Müller, Jörg.; Müller, Jörg.; Levy, Renato.; Levy, Renato. (Lecture Notes in Business Information Processing,, 2012)
The ATOP (Agent-Based Technologies and Applications for Enterprise Interoperability) workshop series focuses on technologies that support interoperability in networked organizations, on successful applications of these technologies, and on lessons learned. In particular, ATOP brings together research combining ideas from MDA and SOA with agent technologies. The ATOP 2009 and 2010 workshops were held at the AAMAS conferences in Budapest, Hungary, in May 2009, and in Toronto, Canada, in May 2010.The 11 papers presented here were carefully reviewed by three members of the international Program Committee and selected out of 25 contributions to the workshops. The topics covered are modeling interoperable systems; semantic approaches to enterprise interoperability; and interoperable business processes and business interactions. These papers are completed by an invited contribution reporting on OMG agent standardization.The main goal was to collect approaches for the application of agent technologies in these areas. Current trends in the development of agent technologies are compared with recent developments in service-oriented and model-driven system design, with respect to their ability to solve interoperability problems.